Identifying Recall Under Sedation by a Novel EEG Based Index of Attention—A Pilot Study - Baron Shahaf, Dana; Weissman, Avi; Priven, Leonid; Shahaf, Goded (Frontiers in Medicine, 2022)
Overview: Recall is an accepted consequence of sedation. EEG-based technologies may be limited in identifying recall under sedation (RUS). We developed a novel index for attentional effort, the cognitive effort index (CEI), which is derived in real-time from one forehead EEG channel, and assessed whether it could differentiate between patients with or without RUS. Methods: EEG was sampled from 2 groups: 1. Patients undergoing sedation (n=25); 2. Patients undergoing general anesthesia (GA, n=13, negative control for recall). In recovery, recall was assessed using the BRICE questionnaire. Results: Of the 25 sedated patients, 11 experienced recall. The CEI marker was high (>0.6) during significantly longer periods in patients with recall, compared to sedated patients or patients under GA without recall. Moreover, the increase in CEI was evident mainly toward the end of the procedure. Conclusion: RUS seems to associate with higher level of attention, which is identified in real-time by the easy-to-extract CEI marker.